Project-Based Learning in Arabic Speaking Instruction: Examining the Role of Communicative Approach and Learner Personality Differences - Maijusnawita; Nurhidayati; Muhammad Khasairi (Postgraduate of IAIN Metro Lampung Indonesia, 2026)
Arabic language learning at the Madrasah level continues to face challenges, particularly in developing students’ speaking skills, which are influenced by pedagogical approaches and learners’ personality types. This study aims to examine the effect of Project-Based Learning (PjBL) using a communicative approach on Arabic speaking skills and to analyze differences in learning outcomes between extroverted and introverted students. The research employed a quasi-experimental design involving an experimental and a control group, with ninth-grade students of MTsN 1 Sijunjung selected through purposive sampling. Data were collected through pretest and posttest speaking assessments, classroom observations, and personality questionnaires using the Eysenck Personality Inventory. The findings reveal that students taught through PjBL demonstrated a significantly greater improvement in speaking skills compared to those taught using conventional methods. Statistical analysis confirmed a significant increase in the experimental group, while the control group showed no meaningful improvement. Furthermore, the PjBL-based communicative approach was effective for both extroverted and introverted learners. This study highlights the novelty of integrating PjBL with personality-based analysis and suggests its potential as an effective strategy for enhancing Arabic speaking proficiency across diverse learner characteristics.